2008
DOI: 10.1111/j.1751-553x.2007.00906.x
|View full text |Cite
|
Sign up to set email alerts
|

A strategy of splitting individual high volume cord blood units into two half subunits prior to processing increases the recovery of cells and facilitates ex vivo expansion of the infused haematopoietic progenitor cells in adults

Abstract: This study was designed to maximize the recovery of the desirable cell populations contained in the cord blood (CB) freezing bag, in order to optimize donor selection for adolescents and adults. To evaluate this hypothesis, high volume CB units (CBUs) were categorized into three volume collection groups (120-139, 140-159 and >or=160 ml) and were randomly split before volume reduction into two half low volume CBUs; (a) and (b). Using the SEPAX Cell Processing System, all CBUs were standardized to 26 ml. In 128 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…Taking these factors into consideration, this work seeks to test the theory that 21 mL (a standard volume for volume-reduced UCB) is the optimal final volume for all UCB units regardless of the initial number of TNC or initial collected volume. Previously, Papassavas et al [12] have shown that with the use of the Sepax system, splitting large units of UCB into 2 smaller volume units before processing increased TNC, mononuclear and CD34þ recoveries. Solves et al [13] also showed that in systems other than Sepax, the increase in volume of buffy coat collected increased the yield of TNC.…”
Section: Variability In Incoming Ucb Unitsmentioning
confidence: 99%
“…Taking these factors into consideration, this work seeks to test the theory that 21 mL (a standard volume for volume-reduced UCB) is the optimal final volume for all UCB units regardless of the initial number of TNC or initial collected volume. Previously, Papassavas et al [12] have shown that with the use of the Sepax system, splitting large units of UCB into 2 smaller volume units before processing increased TNC, mononuclear and CD34þ recoveries. Solves et al [13] also showed that in systems other than Sepax, the increase in volume of buffy coat collected increased the yield of TNC.…”
Section: Variability In Incoming Ucb Unitsmentioning
confidence: 99%
“…Furthermore, the use of semi-automatic CB processing systems significantly reduces the risk of contamination and damage of CB container [18]. Since 2000 along with the use of semi-automatic systems there were used fully automatic ones, such as Sepax S-100 (Biosafe, Switzerland) [19,20]. Using this cell separator, a number of manipulations with CB is reduced comparing to the semi-automatic systems.…”
Section: Isolation Of Nucleated Cells Fraction From Umbilical Cord Blood -Choice Of Methodsmentioning
confidence: 99%
“…To ensure safety and reproducibility, for MNC separation from 105 fresh CB samples, an automated cell‐processing system (Sepax, Biosafe, Eysins, Switzerland) was used (UCB‐HES protocol), with a cell separation kit (CS‐490, Sepax; a closed system of three bags: buffy coat, plasma, and red blood cell [RBC] collection bags), which was connected to the CB collection bag with a sterile docking system (TCD, Haemonetics, Braintree, MA), similar to a methodology described previously . After removal of samples for quality control (QC) testing, hydroxyethyl starch (6% HES in 0.9 NaCl [130 kDa]; Fresenius Kabi, Bad Homburg, Germany) was added to the CB collection bag at a final concentration of 20% (vol/vol), 20 minutes before starting the process.…”
Section: Methodsmentioning
confidence: 99%